Educational landmarks of philosophy and science - Filina, Iryna (Actual Problems of Mind, 2017)
The paper attempts at evaluating an influence of philosophy and science to the world-view formation of modern youth through university education. The author seeks to determine the aspects of a new level of a relative rivalry between philosophy and science in the modern information society.